Constructing Shandong Folk Music Pipa Workbook for Teaching Pipa Students at the College of Arts in Shandong Agricultural University, the People’s Republic of China - Yuqian, Zhang; Yodwised , Chutasiri; Khunthongchan, Prasert (Journal of Roi Kaensarn Academi, 2024)
The purpose of this study is: (1) To study the characteristics of Shandong folk music. (2) To develop the pipa teaching workbook of Shandong folk music. (3) To teach Shandong folk music pipa workbook to the students in our experimental group. (4) To evaluation from using effect Shandong folk music pipa workbook.This study adopts qualitative and quantitative research methods. In the qualitative study, experts were interviewed, and specific repertoire suitable for the third year pipa students was developed based on the experts’ interviews, with the aim of improving students’ interest in learning Shandong folk music and their playing ability, and observing students’ learning dynamics. In the quantitative study, through the IOC’s evaluation of the Shandong Folk Music Pipa lesson Plan, 5 samples from the third year were selected from 15 pipa students in the Art College of Shandong Agricultural University for the experiment. In conjunction with the Shandong Folk Music Pipa Lesson Plan, the students’ learning effects of using the Shandong Folk Music Pipa Lesson Plan were examined by collecting and comparing test scores through formative tests (twice) and summative tests. The results show that the Shandong folk music pipa workbook covers the basic knowledge, performance skills and historical of Shandong folk music. Among them, the teaching workbook for college students fully considers students’ interests and learning characteristics in content, which makes the teaching guide more practical and operational. The results of three tests show that: Shandong folk music pipa workbook has a good guiding role in improving the ability of Shandong students to learn Shandong folk music, This Shandong folk music pipa workbook is successful and can provide some reference experience for other universities.